Sustainability - Oriented Innovation and Performance of Small and Medium Enterprises in South Africa - FATOKI, Olawale (Journal of Environmental Management and Tourism, 2019)
The purpose of this study is to investigate the effect of sustainability-oriented innovation (SOI) on the performance of small and medium enterprises (SMEs) in South Africa. The study adopted a multi-dimensional measure of performance (financial, social, environmental, innovation and quality). The study used the quantitative research approach and the descriptive and causal research design. Data was collected from one hundred and ninety eight owners/managers of SMEs in the manufacturing sector. The cross-sectional survey method (self-administered questionnaire) was used for data collection. The participants in the study were conveniently sampled. Descriptive statistics, factor analysis, correlation and regression analysis were used for data analysis. The Cronbach’s alpha was used as a measure of reliability. The findings of the study indicate that economic, environmental and social dimensions of SOI have significant positive relationships with the five measures of performance. Limitations, areas for further study and recommendations to improve the SOI of SMEs are suggested.